(untitled) (Faridpur Medical College Journal, 2026)
Background: Metabolic dysfunction–associated steatotic liver disease (MASLD), formerly non-alcoholic fatty liver disease (NAFLD), is the most prevalent chronic liver disease worldwide and a leading cause of cirrhosis, hepatocellular carcinoma, and liver transplantation. Despite its growing burden, pharmacological treatment options remain limited, and existing evidence is heterogeneous. This systematic review aimed to critically evaluate the efficacy and safety of pharmacological therapies in improving histological and metabolic outcomes among adults with MASLD/NAFLD. Results: Twenty-three studies met the inclusion criteria, encompassing randomized controlled trials, phase II–III studies, and real-world cohorts. Pharmacological agents targeting metabolic pathways, particularly incretin-based therapies, fibroblast growth factor analogues, and thyroid hormone receptor-β agonists, demonstrated the most consistent improvements in hepatic steatosis, metabolic parameters, and composite efficacy endpoints. Histological benefits, including resolution of steatohepatitis and improvement in fibrosis, were most evident in longer-duration trials with biopsy-confirmed populations. Safety profiles were generally acceptable, with predominantly mild to moderate gastrointestinal adverse events; serious adverse events were uncommon. Conclusions: Pharmacological therapies targeting systemic metabolic dysfunction offer the greatest therapeutic promise for MASLD. While several agents demonstrate meaningful histological and metabolic benefits with acceptable short-term safety, long-term outcomes and optimal treatment strategies require further investigation. Faridpur Med. Coll. J. 2026;21(2): 51-60